Incidence of football injuries and complaints in different age groups and skill-level groups - Peterson, L.; Junge, A.; Chomiak, J.; Graf-Baumann, T.; Dvorak, J. (The American Journal of Sports Medicine, 2000)
In this study, the incidence of football injuries and complaints as related to different age groups and skill levels was studied over the period of 1 year. All injuries and complaints as well as the amount of time players spent in training and games were recorded. All injured players were examined weekly by physicians, and all injuries were assessed according to the International Classification of Diseases (ICD-10), which describes them in terms of injury type and location, the treatment required, and the duration of subsequent performance limitations. A total of 264 players of different age groups and skill levels was observed for 1 year. Five hundred fifty-eight injuries were documented. Two hundred sixteen players had one or more injuries. Only 48 players (18%) had no injury. The average number of injuries per player per year was 2.1. Injuries were classified as mild (52%), moderate (33%), or severe (15%). Almost 50% of all injuries were contact injuries; half of all the contact injuries were associated with foul play. The majority of injuries were strains and sprains involving the ankle, knee, and lumbar spine. Nearly all players (91%) suffered from complaints related to football. Only 23 players reported no injuries and no complaints. Prevention programs, fair play, and continuing education in techniques and skills may reduce the incidence of injuries over time.